Students Perception on Blended Learning - Sophia Binnendyk (Peneliti.net, 2021)
This study aims to perceive the students understanding, point of view, action and expectation toward implementation of blended learning in ELT teaching learning process in English Education Study Program of Language and Art Department , Teachers Training and Educational Sciences Faculty, Pattimura University in Ambon. Students data on perception were collected using closed-ended questionnaire and guided-interview. The data gathered from in depth interview were analyzed qualitatively , while the data obtained from questionnaire were analyzed and interpreted using interval analysis. The results showed that the students had positive perception about the implementation of blended learning. They understand the way blended learning was implemented, they had positive point of view, actions toward blended learning, and they expect the improvement on several aspects of blended learning implementation. Inspite of the challenges that exist in the implementation of blended learning such as the requirement to master the devices/tools of online learning, the unstable internet connection, online activities were meaningful for the students. It has favourable influence on their independence and confidence in learning. Feedback from the lecturer on the students’ tasks and performance are crucial to be paid attention in the implementation of blended learning. Lectures engaged in the development of blended learning need to pay more attention to the ways in which they develop and integrate online and face-to-face materials